Bioassays currently available for evaluating the biological potency of pharmaceuticals in treated wastewater - Vasquez, Marlen; Michael, Irene; Kümmerer, Klaus; Fatta-Kassinos, Despo (My University, 2016)
Water deprivation with regard to quantity and quality is one of the most important environmental problems of the century. The increasing demand of water resources puts pressure on the utilization of alternative sources such as treated wastewater. In the context of "reduce, reuse, and recycle," the inclusion of treated wastewater in the water cycle seems a promising practice for water management. The lack of general acceptance of stakeholders and public, however, still hinders the widespread application of wastewater reuse. A reason for this is, among others, the presence of contaminants of emerging concern in treated wastewater. This has led to an increased concern about direct and indirect effects to the environment and possible implications to human health. The development and application of bioassays able to identify and quantify the biological potency of treated wastewater is an ongoing research effort, especially when taking into consideration that a plethora of contaminants exist and interact in this complex matrix. This chapter summarizes available literature regarding the sensitivity of currently applied bioassays for assessing biological effects of treated wastewater and their correlation with chemical analysis. The focus is on pharmaceuticals since they represent one of the major groups of contaminants of emerging concern with many unanswered questions currently in place.
Keywords: Effect-directed bioassay; Pharmaceutical; Toxicity; Wastewater reuse